IMPLEMENTASI METODE TALAQI DALAM PEMBELAJARAN TAHFIZH ALQUR’AN DI SEKOLAH RENDAH ISLAM INTEGRASI AL-QUDWAH, SELANGOR, MALAYSIA - Alamsyah Kamil Waruwu; Munawir Pasaribu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
One traditional method in the process of learning the Qur'an is the talaqi technique, which emphasizes the direct transmission of Qur'an recitation from the instructor to the student. This study aims to describe the application of this technique in Quran memorization activities, identify supporting and hindering factors, and assess its impact on students' memorization skills and character development. The research method is qualitative and descriptive, conducted at Al-Qudwah Integrated Islamic Elementary School, Selangor, Malaysia. The subjects involved the principal, tahfizh teachers, and students, with a focus on the application of the talaqi technique. Data were collected through field observations, question and answer sessions, and document collection, analyzed using an interactive model that included simplification, presentation, and conclusion drawing, with validity maintained through triangulation. The results show that the talaqi technique is applied systematically through the stages of reading, imitating, repeating memorized verses, and direct correction by the teacher, supported by teacher competence, student enthusiasm, and school rules and facilities. Obstacles include variations in students' memorization abilities, time constraints, and a lack of perseverance in practicing at home. This technique has positive effects, such as improving reading quality, memorization fluency, and Islamic character building, including discipline, patience, and responsibility. The study concluded that the talaqi technique remains very useful and efficient for learning to memorize the Qur'an in formal Islamic elementary schools.